2023
DOI: 10.1039/d3cc03791f
|View full text |Cite
|
Sign up to set email alerts
|

Fully tuneable ethylene–propylene elastomers using a supported permethylindenyl-phenoxy (PHENI*) catalyst

Clement G. Collins Rice,
Louis J. Morris,
Jean-Charles Buffet
et al.

Abstract: Using a highly active supported permethylindenyl-phenoxy (PHENI*) titanium catalyst, high molecular weight ethylene–propylene (EPM) and and ethylene–propylene–diene (EPDM) elastomers are prepared with tuneable compositions using slurry-phase catalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Recently, we reported solid-supported group four permethylindenyl-phenoxy (PHENI*) catalysts, which display outstanding performance for ethylene and propylene polymerisation, producing ultrahigh molecular weight homopolymers, 52,53 and tuneable copolymers. 54 In the latter case, ethylene–propylene copolymers were produced with polymer composition almost exactly corresponding to the feed ratio of gaseous monomers.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported solid-supported group four permethylindenyl-phenoxy (PHENI*) catalysts, which display outstanding performance for ethylene and propylene polymerisation, producing ultrahigh molecular weight homopolymers, 52,53 and tuneable copolymers. 54 In the latter case, ethylene–propylene copolymers were produced with polymer composition almost exactly corresponding to the feed ratio of gaseous monomers.…”
Section: Introductionmentioning
confidence: 99%
“…Following the synthesis of permethylindenyl-based metallocenes, Williams et al reported the synthesis of permethylindenyl CGC analogues of the type Me 2 SB­( R N,I*)­TiCl 2 ({(η 5 -C 9 Me 6 )­Me 2 Si­( R N)}­TiCl 2 , where I* = η 5 -C 9 Me 6 ). , Ethylene polymerization activities up to three times that of the Cp* (η 5 -C 5 Me 5 ) derivatives were reported, with more electron-donating amido fragments shown to result in increased catalytic activities . More recently, we have reported the permethylindenyl-phenoxy (PHENI*) ligand, offering exceptional performance in olefinic polymerizations producing ultrahigh-molecular-weight homopolymers and highly tunable copolymers. …”
Section: Introductionmentioning
confidence: 99%